Analisis Pelayanan Publik pada Kepolisian Resor Sidrap (Studi di Sentra Pelayanan Kepolisian Terpadu) - Z, Sufriadi; Jamaluddin, Jamaluddin; Nilwan, Andi; Nur, Muhammad; S, Muliani; Mustanir, Ahmad (Policy, Law and Political Research Center, 2025)
This study examines the effectiveness of the Sidrap Police Integrated Police Service Center (SPKT) public services, identifies factors influencing service responsiveness, and measures public satisfaction with the services received. Using a descriptive qualitative approach, the research was conducted at the Sidrap Police SPKT at Jalan Bau Massepe No. 1 Pangkajene, Maritengae District, Sidenreng Rappang Regency. Data were collected through in-depth interviews, structured questionnaires, direct observation, and documentation analysis. Data were analyzed using the Huberman interactive model, including data reduction, presentation, and conclusion drawing. The results showed that 85% of respondents rated the Sidrap Police SPKT service as effective. Officer friendliness, service speed, easy access to information, and responsiveness were the main factors in the positive assessment. However, aspects of information transparency and infrastructure still require improvement. Factors affecting service responsiveness include the completeness of facilities, technology training for officers, workload, and leadership support. The level of community satisfaction is in the high category, with the average score of service components ranging from 3.7 to 4.4 out of a scale of 5. This research provides practical recommendations for the development of a more responsive police public service model that has a high score.